Akuntansi Dari Kacamata Syariah Dan Ekonomi Islam - Musta’an Musta’an; Herlina Kusuma Wardani (Jurnal Ilmiah Ekonomi Islam, 2017)
Accounting is information submitted by companies through financial statements to provide a very clear picture of the various circumstances or conditions of the company. The purpose of this research is to know the concept of accounting in terms of the eyes of sharia and Islamic economics. The concept of Islamic accounting emerged long before the conventional accounting concepts that existed to date, even Islam itself has made a series of rules in accounting that have never been thought of by conventional accounting experts. The method used in this research is by using library method. Syariah Islam strongly supports the existence of accounting activities in every activity of activities undertaken by humans especially related to financial problems. The Islamic economic system studies and studies the people's economy by making the Qur'an and Hadith as its basis. Similarly, accounting, because the science of accounting related to the economic activities of people who have been described also in the Qur'an and Hadith. Islamic accounting in it covers issues that are not commonly thought of by capitalist accounting or conventional accounting. Human behavior while in the world will be judged in the afterlife. So that accounting is considered and considered as one of hisab or derivasinya is to advocate the good and forbid something bad. How to cite:  Musta’an, M., & Wardani, H. (2017). Akuntansi Dari Kacamata Syariah Dan Ekonomi Islam. Jurnal Ilmiah Ekonomi Islam, 3(03), 181-185. doi:http://dx.doi.org/10.29040/jiei.v3i03.130